4/x²-9 - 2/x²+3x
упростить выражение
и подобно расписать действие

Nastik6634 Nastik6634    1   06.09.2021 00:12    0

Ответы
Имом Имом  20.11.2021 20:27

Пошаговое объяснение:

\frac{4}{ {x}^{2} - 9} - \frac{2}{ {x}^{2} -+3x } = \\ = \frac{4}{( {x} - 3)(x + 3)} - \frac{2}{x( {x}+3) } = \\ = \frac{4x}{x( {x} - 3)(x + 3)} - \frac{2(x -3)}{x( {x}- 3) (x + 3)} = \\ = \frac{4x - 2(x -3)}{x( {x}- 3) (x + 3)} = \\ = \frac{4x - 2x + 2 \cdot3}{x( {x}- 3) (x + 3)} = \\ = \frac{ 2x +6}{x( {x}- 3) (x + 3)} = \frac{ 2 \cancel{(x +3)}}{x\cancel{(x + 3)} (x -3)} = \\ = \frac{2}{x(x - 3)} = \frac{2}{ {x}^{2} - 3x }

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика